2004
DOI: 10.1167/iovs.04-0719
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Spatiotemporal Characterization of Spontaneous Ca2+Sparks and Global Ca2+Oscillations in Retinal Arteriolar Smooth Muscle Cells

Abstract: Retinal arterioles generate Ca(2+) sparks with characteristics that vary during different phases of the spontaneous Ca(2+)-signaling cycle. Sparks summate to produce sustained Ca(2+) transients associated with contraction and thus may play an important excitatory role in initiating vessel constriction. This deserves further study, not least because Ca(2+) sparks appear to inhibit contraction in many other smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 35 publications
3
37
2
Order By: Relevance
“…19,20 Although the term oscillation has been used to describe all prolonged elevations in [Ca 2ϩ ] (Ͼ0.5 seconds), these cannot be distinguished from propagating Ca 2ϩ -waves in transverse line scan recordings. The time course of changes in F/F 0 , spatially averaged across the width of each cell, was plotted using ImageJ software (developed by Wayne Rasband, National…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20 Although the term oscillation has been used to describe all prolonged elevations in [Ca 2ϩ ] (Ͼ0.5 seconds), these cannot be distinguished from propagating Ca 2ϩ -waves in transverse line scan recordings. The time course of changes in F/F 0 , spatially averaged across the width of each cell, was plotted using ImageJ software (developed by Wayne Rasband, National…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that high-speed Ca 2ϩ -imaging reveals brief, localized subcellular Ca 2ϩ -signals known as Ca 2ϩ -sparks in both rat and pig retinal arterioles 20,21 ( Fig. 2A).…”
Section: Cellular and Subcellular Ca 2؉ -Signaling Responses To Et1mentioning
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, significant progress has been made, particularly toward understanding mechanisms of rhythmicity, myogenic tone, and ion transport (11,12,14,17,20,25,26,31,33,34). An area of particular interest is calcium signaling (10,15,26,38). Calcium has a pivotal role in regulating contraction but also emerging importance as a regulator of gene expression and cellular phenotype (2,50).…”
mentioning
confidence: 99%